AUTONOMY OF EDUCATIONAL RESEARCHERS IN THEIR PRACTICES OF USING ARTIFICIAL INTELLIGENCE - Machado, Elaine da Silva; Arruda, Sergio de Mello; Passos, Marinez Meneghello (Seven Editora, 2025)
In this study, we characterize the relationships that educational researchers established with autonomy in situations in which they used Artificial Intelligence (AI) in their scientific practices. The methodological procedures were based on the qualitative approach and the Content Analysis (CA) technique, considering the categories of an analytical instrument that we developed. The data came from reports presented by the researchers regarding their research practices and their relationships with autonomy and AI. Among the results, we characterize the researchers' relationships with autonomy, in situations of AI use linked to the exercise and non-exercise of ethics, political skills, and the development of their own knowledge. The situations of AI use involved eleven types of practices carried out by the researchers, conditioned by criteria related to maintaining the scientific rigor of their productions. We conclude with respect to the characterizations and contributions of autonomy and the use of AI for the training and work of educational researchers, and the importance of establishing standards that determine conditions and limits for the application of AI in educational scientific practices. For example, regulating the use of AI through systematic review of productions by researchers/advisors, with attention to the authenticity and veracity of the data and knowledge produced, and to the requirements of objectivity, theoretical rigor, logical coherence and methodological consistency. Finally, we propose possible directions for future studies.DOI: https://doi.org/10.56238/sevened2025.026-018